The United States immigration laws: History of a nation set up by migrants - Bonomi, Federico (Vergentis, 2019)
The purpose of my paper is to consider a set of policies concerning flows adjustment and naturalization of immigrants. The starting point of my analysis is the Naturalization Act of 1790, the first immigration law of the US government, which inspired the subsequent ones. I have conducted a more detailed investigation into federal measures since 1882, the year of Chinese Exclusion Act, passing through the legislation of the period between 1920 and 1930, influenced by a marked protectionism, to arrive to the acts of 1965, which dismantled the system of national quotas. The goal of my work is to highlight the relationship between the laws and the debate that has been created around them, which involves congress, public opinion, trade unions and associations.